A Robust Step‐Size Control Technique Based on Proportionate Constraints on Filter Update for Acoustic Echo Cancellation. Issue 4 (1st July 2016) - Wu, Chao; Jiang, Kaiyu; Wang, Xiaofei; Guo, Yanmeng; Fu, Qiang; Yan, Yonghong
Abstract : One of the main difficulties in Acoustic echo cancellation (AEC) is that the filter adaptation needs to vary according to different situations such as near‐end interferences and echo path changes. In this paper, we propose a robust step‐size control algorithm in frequency domain. The proposed method is based on the optimization of the square of the bin‐wise a posteriori error. Constraint on the filter update is applied, which contributes to robustness to near‐end interferences of the algorithm. The learning rate formula is derived first and then the relationship between the proposed algorithm and a robust statistics based approach is revealed. The method is extended to the Multidelay block frequency domain adaptive filter (MDF) so as to meet the demand of low delay in practical application. Moreover, the values of the constraints are designed to be updated proportionately to improve the convergence property. Simulation results demonstrate the superiority of the proposed algorithm.